» »


>tg(+)=(tg+tg)/(1tgtg);tg(-)=(tgtg)/(1+tgtg)

>ctg(+)=(ctgctg1)/(ctg+ctg);ctg(+)=(ctgctg+1)/(ctgctg)

>sin+sin=2sin(+)cos(-);sin-sin=2cos(+)sin(-)

>cos+cos=2cos(+)cos(-);cos-cos=-2sin(+)sin(-)

>asinx+bcosx=(>a+b)sin(x+), tg=b/a

>tg >tg=sin(+)/(coscos);ctg >ctg=sin(>)/(sinsin)

>sinsin=coscos=sin(+)sin(-)

>cossin=cossin=cos(+)cos(-)

>sinsin=[cos(-)cos(+)];coscos=[cos(-)+cos(+)]

>sincos=[sin(+)+sin(-)]

>tgtg=(tg+tg)/(ctg+ctg)=-(tgtg)/(ctgctg)

>ctgtg=(ctg+tg)/(tg+ctg)=-(ctgtg)/(tgctg)

>ctgctg=(ctg+ctg)/(tg+tg)=-(ctgctg)/(tgtg)

>sin=((>1cos)/2);sin=(2tg)/(1+tg)

>sin2=2sincos;sin3=3sin4sin

>sin=(1cos2);sin=(3sin sin3) / 4

>cos=[(>1+cos)/2];cos=(1tg)/(1+tg)

>cos2=cossin=12sin=2cos1;cos3=4cos3cos

>cos=(1+cos2);cos=(3cos+cos3)/4

>tg=sin/(1+cos)=(1cos)/sin= ((>1cos)/(1+cos))

>tg=(2tg)/(1tg);tg2=(2tg)/(1tg)=2/(ctgtg)

>tg3=(3tgtg)/(13tg)=tgtg(/3+)tg(/3)

>ctg=sin/(1cos)=(1+cos)/sin=((>1+cos)/(1cos))

>ctg=(ctg1)/2ctg;ctg2=(ctg1)/2ctg=(ctgtg)

>ctg3=(3ctgctg)/(13ctg)

>tg(+)=(sin+cos)/(sincos);tg()=(sincos)/(sin+cos)


:

  • :
    ,
  • :
  • : ²
    > >, > > ( ).
  • :
    . .
  • :
    > , 쳿 ( 1758 ),